2007
DOI: 10.1088/1751-8113/40/7/f01
|View full text |Cite
|
Sign up to set email alerts
|

Kerr–NUT–de Sitter curvature in all dimensions

Abstract: We explicitly calculate the Riemannian curvature of D-dimensional metrics recently discussed by Chen, Lü and Pope. We find that they can be concisely written by using a single function. The Einstein condition which corresponds to the Kerr-NUT-de Sitter metric is clarified for all dimensions. It is shown that the metrics are of type D.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
130
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 66 publications
(136 citation statements)
references
References 14 publications
6
130
0
Order By: Relevance
“…Therefore, from now on we refer to the off-shell spacetime (4.1), without imposing (4.3), as to the canonical metric. The canonical metric is of the special algebraic type D [102] of the higher-dimensional algebraic classification [178], [46], [45]. Let us finally remark that formulas (4.1)- (4.3) are applicable also in D = 3 where one recovers the 2-parametric BTZ black hole [13].…”
Section: Overview Of the Kerr-nut-(a)ds Metricsmentioning
confidence: 99%
See 3 more Smart Citations
“…Therefore, from now on we refer to the off-shell spacetime (4.1), without imposing (4.3), as to the canonical metric. The canonical metric is of the special algebraic type D [102] of the higher-dimensional algebraic classification [178], [46], [45]. Let us finally remark that formulas (4.1)- (4.3) are applicable also in D = 3 where one recovers the 2-parametric BTZ black hole [13].…”
Section: Overview Of the Kerr-nut-(a)ds Metricsmentioning
confidence: 99%
“…In particular, it was proved that, similar to the 4D case, the most general Einstein space admitting the PCKY tensor is the Kerr-NUT-(A)dS spacetime. Meanwhile, it was shown that the Kerr-NUT-(A)dS spacetime is of the algebraic type D of higher-dimensional algebraic classification [102] and that it allows a generalized Kerr-Schild form [38]. By relaxing some of the requirements imposed on the PCKY tensor more general spacetimes were recently discovered [109], [108].…”
Section: Hidden Symmetries In Higher Dimensionsmentioning
confidence: 99%
See 2 more Smart Citations
“…The parameter c n is proportional to the cosmological constant, and the remaining constants c k , c and b µ are related to the rotation parameters, the mass and the NUT parameters. Hamamoto, Houri, Oota and Yasui [14] derived explicit formulas for the curvature and demonstrated that in all dimensions this metric obeys the Einstein equations…”
Section: Higher-dimensional Black-hole Spacetimesmentioning
confidence: 99%